646 PREDICTING RESPONSE TO NEOADJUVANT CHEMOTHERAPY IN PATIENTS WITH OESOPHAGEAL ADENOCARCINOMA. (17th September 2021) - Bott, Rebecca; George, Gincy; McEwen, Ricardo; Zylstra, Janine; Knight, William; Baker, Cara; Kelly, Mark; Griffin, Nyree; Mcaddy, Naami; Maisey, Nick; Van Hemelrijck, Mieke; Gossage, James; et al.
Abstract: : Neoadjuvant chemotherapy is often used prior to surgical resection for oesophageal adenocarcinoma but remains ineffective in a high proportion of patients. The histological Mandard tumour regression grade is used to determine chemoresponse but is not available at the time of treatment decision-making. The aim of this study was to identify factors that predict chemotherapy response prior to surgery. Methods: A prospectively collected database of patients undergoing surgical resection for oesophageal adenocarcinoma from a high-volume UK institution was used. Patients were subcategorised using pathological tumour response into 'responders' (Mandard grade 1–3) and 'non-responders' (Mandard grade 4&5). Multivariable logistic regression analysis was performed to calculate crude and adjusted odds ratios (OR) with 95% confidence intervals (CI) for responder status adjusting for a variety of parameters. Receiver-operator curves (ROC) were calculated. Results: Among 315 patients included, 102 (32%) were responders and 213 (68%) non-responders. A decrease in radiological tumour volume (OR 1.92 95%CI 1.02–3.62; p = 0.05), a 'partial response' RECIST score (OR 7.16 95%CI 1.49–34.36; p = 0.01), a clinically improved dysphagia score (OR 2.79 95%CI 1.05–7.04; p = 0.04) and lymphovascular invasion (OR 0.06 95%CI 0.02–0.13; p = 0.000) influenced responder status. ROC curve analysis for responder status utilising all available parameters had an area under the curve (AUC) of 0.86. Conclusion: This study has highlighted the potential for using pre-defined factors to identify those patients who have responded to neoadjuvant chemotherapy, prior to surgical resection, potentially facilitating a more individualised therapeutic approach.